Well-differentiated extraskeletal chondrosarcoma: about a new case - MAKNI, S.; MAKNI, S. KRICHEN; TRIKI, F. ELYES; MELLOULI, M.; ABID, N.; KALLEL, R.; CHARFI, S.; BOUDAWARA, T. SALLEMI (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2018)
Extraskeletal chondrosarcoma is a rare malignant tumor. The well differentiated histological type, which is found primary in soft tissue, is extremely rare. This report describes the case of a 58 year-old woman presented with a large palpable mass in the right buttock. Imaging studies revealed a well-defined soft tissue mass, with extensive calcification. A histological examination after surgical resection confirmed the diagnosis of well-differentiated extraosseous chondrosarcoma. The outcome was favorable, without recurrence or metastasis.